Laporan Kasus: Tatalaksana Hematoma Akibat Trauma - Fanni Kusuma Djati; Chrystina Kusuma Dewi (Fakultas Kedokteran Gigi Universitas Jember, 2018)
Hematoma is a large collection of extravasation of blood due to trauma, causing a palpable mass. The cause of hematoma is usually due to trauma or due to a systemic bleeding disorder. The differential diagnosis of this lesion is ecchymosis and hemangioma. A strong examination and history are needed to determine the diagnosis. Hematomas usually do not require treatment because of self-limiting. A 19-year-old woman came for control after 1 week of cleaning tartar/scaling. There was a swelling that the patient does not realize is under the dark red tongue with a size of ± 2mm. The patient had no history of systemic disease. OHI-S is good and other objective examinations are within normal limits. Therapy was given in the form of dental health education and evaluation of lesions for ± 1 week. Hematomas were generally caused by trauma resulting in extravasation of blood to the tissues that affect the underlying blood vessels. Hematoma could disappear spontaneously so there is no need for treatment.